A new effective solution for wind farm layout optimisation problem using self-sacrificing artificial bee colony algorithm. (5th September 2022) - Sharma, Nirmala; Sharma, Harish; Sharma, Ajay; Bansal, Jagdish Chand
The wind farm layout optimisation problem (WFLOP) is a complex constrained optimisation problem to find the optimal locations of wind turbines in a wind farm so as to maximise energy output. Artificial bee colony (ABC) is a swarm intelligence-based optimisation algorithm. This paper presents a modified variant of ABC and its application to WFLOP. A new phase inspired by the altruistic behaviour of honeybees is incorporated with ABC to enhance the exploitation capability of the algorithm. Here, a lower fit solution always sacrifices its chance of updating its position for a higher fit solution. The proposed phase is named as self-sacrificing phase and the proposed strategy is termed as self-sacrificing ABC (SeSABC) algorithm. The proposed technique is examined using a set of constrained optimisation functions and applied to solve WFLOP. For a given wind farm, the optimum locations of turbines are obtained and a maximum number of turbines are identified.